ANALISIS KINERJA KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA PADA SEKOLAH TINGGI TEKNOLOGI MUTU MUHAMMADIYAH (STTM M)DI TANGERANG - Suryo Sulistyo; Asrori Mukhtarom (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2020)
This research aims to identify service quality performance to collegestudents, the method used is a surveys customer satisfaction by using random sampling techniqueand Cartesian diagrams byusing SPSS application. The survey was conducted on 235 collegestudents out of a total of 335 collegestudents. Surveys data were analyzed using Cartesian diagramsto identify services and levels of college student satisfaction to the quality of campus services. The results of the study show, in the quadrant I;F2 the appearance of lecturers and employees in the ordinate(5,65, 5,80), F3 the comfort and cleanliness of the lecture hall in the ordinate (5.56, 5,77), F9 Post Graduate education for lecturers and competencies in science in ordinates (5,40, 5,83), F10 the lecturer delivered an interactive and interesting talk in ordinates (4,92, 5,83), F13 Lecturers are willing to prepare teaching materials in the ordinate (5,65, 5,87), F14 lecturer support for student success in the ordinate (5,65, 5,87), shows that students are satisfied and considered important to students. In the quadrant II; F1 LCD, AC and WIFI facilities in the ordinate (4,56 , 5,82), F7 Lecturers on time give talks in the ordinate (4,72, 5,75), F12 Study Program Card will be distributed according to the time specified in the ordinate (4,71, 5,56), F15 friendly administrative staff in the ordinate (4,77, 5,72), means it is unsatisfactory and is considered important for college student, In order to satisfy the student, it must be transferred to the quadrant I. Therefore the factors that are in quadrant II must be improved